Childhood Trauma Is Predictive for Clinical Staging, Alcohol Consumption, and Emotional Symptoms in Patients With Head and Neck Cancer - Sarafim-Silva, Bruna Amélia M. [UNESP]; Duarte, Gabrielle D. [UNESP]; Sundefeld, Maria Lúcia M. M. [UNESP]; Biasoli, Éder Ricardo [UNESP]; Miyahara, Glauco I. [UNESP]; Bernabé, Daniel Galera [UNESP] (Wiley, 2018)
Background: Traumatic events in childhood have been associated with the occurrence of anxiety and depression in adulthood. This relation has been investigated in patients with breast cancer; however, it has been little explored in patients with other types of cancer. The objective of this study was to evaluate the occurrence of childhood trauma in patients with head and neck cancer and its association with clinicopathological variables and anxiety and depression levels. Methods: The study included 110 patients with head and neck squamous cell carcinoma (HNSCC) before they started cancer treatment. Clinicopathological and biobehavioral data were collected from patients' medical records. Anxiety and depression levels were assessed with the Beck Anxiety Inventory and the Beck Depression Inventory, respectively. The Childhood Trauma Questionnaire was used to evaluate the occurrence of traumatic events in childhood. Results: One hundred five patients (95.5%) experienced at least 1 type of childhood trauma. Emotional neglect was the most reported childhood trauma (43.8%), and multiple regression revealed that it was an independent variable for advanced clinical staging (β = 2.15, P =.048) and higher alcohol consumption (β = 2.32, P =.031). Patients with HNSCC who experienced more traumatic events in childhood had an almost 12 times greater chance of increased depression levels during the pretreatment period (β = 11.89; P =.0002). The occurrence of physical child neglect was a predictive factor for increased anxiety levels (β = 4.17, P = 0.029). Conclusions: Traumatic events in childhood are predictive for advanced clinical staging, alcohol consumption, and emotional symptoms in patients with HNSCC, and they should be considered in clinical and psychological intervention strategies during cancer treatment. Cancer 2018;000:000-000. © 2018 American Cancer Society.
Keywords: addiction; anxiety; cancer; child abuse; childhood trauma; clinical staging; depression; emotional symptoms; head and neck cancer; squamous cell carcinoma